A contest of civilizations : exposing the crisis of American exceptionalism in the Civil War era - Lang, Andrew F., 1982- (Littlefield history of the Civil War era., 2021)
Most mid-19th-century Americans regarded the US as an democratic republic that stood apart from a world seemingly riddled with revolutionary turmoil & aristocratic consolidation. Viewing themselves as distinct from & even superior to other societies, Americans considered their nation an unprecedented experiment in political moderation & constitutional democracy. But as abolitionism in England, economic unrest in Europe, & upheaval in the Caribbean & Latin America began to influence domestic affairs, the foundational ideas of national identity also faced new questions. In this sweeping history of political ideas, Andrew F. Lang reappraises the Civil War era as a crisis of American exceptionalism.